2022
DOI: 10.5812/hepatmon.118721
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tenofovir Alafenamide and Entecavir Therapy in Patients with Chronic Hepatitis B Initially Treated with Tenofovir Disoproxil: A Retrospective Observational Survey

Abstract: Background: In chronic hepatitis B patients with or exposed to the risk of osteoporosis or renal dysfunction, switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide fumarate (TAF) or entecavir (ETV) may be the right choice. Objectives: This study aimed to present real-life data in terms of the efficacy and safety of a TAF/ETV treatment change while receiving TDF. Methods: This retrospective study was conducted on 344 adult patients from 10 centers. The data of patients who had changed to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Both the vertebra T score and the femur T score were significantly lower after the pandemic than before the pandemic in the patients who continued TDF treatment. These results are consistent with previous studies (20).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Both the vertebra T score and the femur T score were significantly lower after the pandemic than before the pandemic in the patients who continued TDF treatment. These results are consistent with previous studies (20).…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have reported that long-term use of TDF results in a decrease in BMD and an increase in renal toxicity (20)(21)(22). Patients who changed from TDF to TAF showed a significant improvement in estimated glomerular filtration rate (eGFR) levels and hip and spine T scores (20). In another study, it was observed that after 2 years of TDF treatment, eGFR significantly decreased.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations